Synthesis of surface imprinted polymers based on wrinkled flower-like magnetic graphene microspheres with favorable recognition ability for BSA. (30th May 2021) - Yang, Zuoting; Yang, Ke; Cui, Yuhong; Shah, Tariq; Ahmad, Mudasir; Zhang, Qiuyu; Zhang, Baoliang
Graphical abstract: Highlights: BSA surface imprinted magnetic graphene microspheres are first developed. Fe3 O4 @rGO with wrinkled flower-like structure is selected as matrix. Fe3 O4 @rGO@MIPs exhibit easy and rapid separation under a magnet. The capacity of Fe3 O4 @rGO@MIPs for BSA reaches 317.58 mg/g in 60 min. Fe3 O4 @rGO@MIPs possess high specificity to BSA from actual samples. Abstract: Nowadays, the employing of molecular imprinting technique in the analysis and separation of proteins from complex biological samples has been widely favored by researchers. To enrich the types of surface protein imprinted materials and expand the application fields of graphene materials, novel surface molecular imprinted polymers (MIPs) based on magnetic graphene microspheres Fe3 O4 @rGO@MIPs are first synthesized in this paper. Fe3 O4 @rGO@MIPs are prepared by oxidative self-polymerization of dopamine on the surface of magnetic graphene (Fe3 O4 @rGO) composite microspheres. Bovine serum albumin (BSA) is selected as protein template. Fe3 O4 @rGO microspheres with wrinkled flower-like structure are obtained by compounding Fe3 O4 and graphene oxide in an appropriate ratio via the method of high-temperature reduction self-assembly. The microspheres exhibit promising dispersibility, high external surface area, rich pore structure, and sufficient magnetic properties. These advantages not only prevent the agglomeration of imprinted microspheres in the aqueous phase, which is conducive to contact and static adsorption, but also increase the amount of protein imprinting. Additionally, sufficient magnetic properties ensure fast and effective separation of the adsorbents. While the adsorption capacity is increased, the separation procedure becomes simple. The binding capacity of Fe3 O4 @rGO@MIPs for BSA can reach 317.58 mg/g within 60 min, and the imprinting factor (IF) is 4.24. More importantly, Fe3 O4 @rGO@MIPs can specifically recognize the target BSA from the mixed proteins and the actual sample. There is no significant decrease in the adsorption amount, IF, and magnetic properties after eight runs. It is promising to be used in the separation of proteins from the actual biological samples.